Pengaruh Penggunaan Aplikasi Muamalat Din terhadap Minat dengan Metode Tam pada Nasabah Bank Muamalat Medan - Lutfia Tri Aryanti (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2023)
This study aims to determine the effect of perceived usefulness, perceived ease of use and trust on the use of the Muamalat DIN application. This type of research is quantitative. The data used in this study are primary data obtained through questionnaires with variable instruments using a Likert scale which were distributed to respondents totaling approximately 100 people. The data analysis technique used is a data analysis test which consists of a validity test, reliability test, classic assumption test which consists of a normality test, multicollinearity test and heteroscedasticity test, and also uses multiple linear regression analysis, which consists of F test, T test and test the coefficient of determination (R2) using the SPSS data processing application version 26. The results of this study indicate that there is no effect of perceived usefulness on customer interest in using the Muamalat DIN application. There is a significant effect of perceived ease of use on the interest in using the Muamalat DIN application. There is a significant influence of trust on the interest in using the Muamalat DIN application. And there is a significant positive effect between Perceived Usefulness, Perceived Ease of Use and Trust on interest in using the Muamalat DIN application. Keywords: Interest, Technology Acceptance Model (TAM), Muamalat Application